The Effect of the Addition of Active Digester Effluent for Start-up Accelerator in Anaerobic Digestion of Soybean Curd Industry Waste Water (Basic Research for Biogas Power Generation) - Wiratni Budhijanto; Arini Wresta; Arini Wresta (National Research and Innovation Agency, 2012)
Biogas production from soybean curd industry waste water was studied in laboratory scale to improve the application of anaerobic digestion process. The problem with the soybean curd waste water was the fact that it does not sufficiently contain anaerobic microorganisms required in biogas production. Therefore, it is necessary to add a well-developed population of anaerobic microorganisms to accelerate the start-up of the anerobic digestion. This research was aimed to verify the influence of the addition of active digester effluent into the soybean curd waste water batches in an anaerobic digestion process. Batch experiments were done in two digesters. The first digester was only fed with soybean curd waste water while the second digester was fed with soybean curd waste water and active digester effluent from a digester processing cow manure which was very rich in anaerobic microorganism consortium. The results indicated that soybean curd industry waste water did not contain methanogenic bacteria but there existed some acidogenic bacteria. The addition of active digester effluent accelerated the anaerobic digestion start-up and directed the process pathway towards methanogenic process so that more methane was obtained. The high methane content obtained (more than 64% volume) was very potential for power generation. The capacity of soybean curd industry must be as high as 697.13 kg soybean per day to generate the electric energy of 8.4 kWh.